Flashdance [videorecording (DVD)] - Beals, Jennifer; Nouri, Michael; Skala, Lilia (Paramount Home Entertainment, 2017)
Alex Owens is a fiercely determined eighteen year old with one all consuming dream: to study at the Pittsburgh Conservatory of Dance. Working during the day as a welder and at night as an exotic dancer, Alex bravely pursues her dream. As she undertakes an unforgettable journey that reveals the power of her convictions, she will also learn the meaning of love.